(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Krishna Kanta Handiqui State Open University (KKHSOU) plays an important role in providing open and Distance Learning (ODL) opportunities in Assam. This study examines the functioning of KKHSOU study centers in Nagaon district, focusing on key aspects such as infrastructure, academic support, and learner enrollment trends. Data was collected from selected study centers through surveys, interviews, and document analysis to evaluate the effectiveness of these centers in delivering quality education. The study highlights the role of physical and technological infrastructure, faculty support, and student services in enhancing the learning experience. It also identifies key challenges, including resource constraints, administrative hurdles, and the need for better technological integration. The findings provide insights into the strengths and limitations of KKHSOU’s study centers and offer recommendations for improving the accessibility and efficiency of ODL in the district.